Vitamin D Deficiency in Children with Chronic Renal Disease - Dyussenova , S. B.; Gordiyenko , M. Y.; Serikova, G. B.; Turlybekova, S. A.; Issayeva, A. A.; Yerimbetova, N. A; Goroshko, V. O. (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Vitamin D is essential for children and adults for healthy bone growth. Lack of this vitamin in children can cause rickets, and in adults, softening of the bones and an increased risk of fractures. Vitamin D deficiency can cause immune disorders, increased susceptibility to infections, the development of certain types of cancer, diabetes mellitus, and cardiovascular diseases. AIM: The article presents the literature data and the results of our own research on the analysis of the relationship between chronic kidney disease (CKD) and Vitamin D provision in children from 1 to 17 years old. The aim of the study was to establish the level of Vitamin D in children with different stages of CKD. METHODS: Between January 2020 and September 2020, we examined 40 children (16 boys and 24 girls). The patients’ age ranged from 1 to 17 years inclusive. RESULTS: Vitamin D deficiency was found in 62.5% of children with CKD. Vitamin D deficiency was noted in 25% of cases. The prevalence of Vitamin D deficiency correlates with a decrease in glomerular filtration rate. CONCLUSION: Determination of Vitamin D level in children with CKD is important for timely correction and prevention of further progression of CKD. Timely substitution therapy will improve the quality of life of a child with CKD and prevent the development of complications.